Solar Panel Energy With Smart Irrigation System - Mohapatra, Rashmita; Pathare, Rushil; Gupta, Vansaj; Nair, Sreyas (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
In today’s climatic conditions such as unprecedented amounts of rain and frequent heat waves, cultivating has become a tedious task. Predicting nature’s next move is not easy but what we can do is minimize its effect on the yield. There are so many regions that receive excessive rainfall, suffer frequent flash floods and scorching heat. To adapt to these conditions, sensor networks can be deployed in the fields and the available resources should be used as efficiently as possible. In order to fulfill this requirement, power storage capable of storing energy efficiently from solar panels and an irrigation controller which monitors the land, be it for farm, gardening or horticulture with little to none intervention in certain aspects. The existing products in the market have proprietary parts, features and they don’t endorse cross-compatibility with other products. Keeping the design open source and easy to work promotes recycling and reparability something essential in the current time of global silicon shortage. Farmers or gardeners often don’t know the amount of water and the intervals of irrigation for many exotic and domestic species of plants, they then end up growing crops such as wheat and rice which need flooding of the field, the cultivation of these species can be promoted and be made easy with the project. Telemetry and connected technologies are part of every system these days. The project monitors various parameters and depending on the conditions, will carry out necessary action such as irrigation in only amounts required by the field. This is possible through PWM control of motors coupled with valves.